Peran Guru dalam Mengembangkan Keterampilan Sosial Siswa di SDN 1 Limboto - Kinanti Labantu; Thamrin A Kum; Lia Nurhayati (Research Review: Jurnal Ilmiah Multidisiplin, 2026)
This study aimed to describe the role of teachers in developing students’ social skills at SDN 1 Limboto. The study employed a qualitative approach with a case study design. The research subjects consisted of the principal, fourth-, fifth-, and sixth-grade teachers, as well as students at SDN 1 Limboto. Data were collected through observation, interviews, and documentation. Data validity was ensured through source, technique, and time triangulation, while data analysis referred to the interactive model of Miles, Huberman, and Saldaña, which includes data reduction, data display, and conclusion drawing. The findings revealed that teachers play a significant role in developing students’ social skills through role modeling in communication, collaborative learning, positive emotional relationship building, positive reinforcement, and conflict mediation among students. These strategies helped students improve communication skills, cooperation, empathy, tolerance, and constructive conflict resolution. Furthermore, teachers functioned not only as knowledge transmitters but also as social facilitators and emotional mentors in students’ character development. The study indicates that social skills development should be continuously integrated into the learning process and school culture to support character building and students’ social competencies at the elementary school level.